PENGARUH VARIASI SUHU DAN WAKTU TINGGAL PIROLISIS TERHADAP NILAI KADAR AIR ARANG KARBON DARI BIOMASSA BATANG UBI KAYU - Lutfi Dwi Hernawan (ELEMEN : JURNAL TEKNIK MESIN, 2025)
Cassava stem waste, abundant in Indonesia (90% post-harvest), shows high potential as a carbon raw material due to its lignocellulose content. This research investigates the effect of pyrolysis temperature and residence time on the moisture content of the resulting carbon charcoal. Using an experimental method with a fixed-bed reactor, cassava stem biomass was pyrolyzed at varying temperatures of 300℃ and 400℃, and residence times of 15 minutes and 30 minutes, and then tested for its moisture content. The results indicate that the charcoal's moisture content tends to increase with rising temperature and residence time, attributed to an increase in the charcoal's hygroscopic properties. Nevertheless, all testing variations produced charcoal with a moisture content below 15% as per SNI 06-3730-1995, with the lowest moisture content (3.8%) achieved at 300℃ and 15 minutes.